Metaldehyde removal from drinking water by adsorption onto filtration media: mechanisms and optimisation - Rolph, Catherine A.; Jefferson, Bruce; Hassard, Francis; Villa, Raffaella (Cranfield University, 2018)
Trace micropollutants should be removed during drinking water production without increasing the disinfection-by-product formation potential or energy demand of the treatment process. We demonstrate the efficacy of different filtration media to remove metaldehyde through controlled batch experiments on water augmented with metaldehyde. Equilibrium concentrations of metaldehyde and surrogate organics were successfully described by the Freundlich isotherm. Metaldehyde can be attenuated to varying degrees with activated carbon and sand with an active and inactive biofilm with kf values ranging from 0.006–0.3 (mg g−1)(L mg−1)1/n. The presence of the active biofilm improved metaldehyde adsorption by sand media, due to additional biosorption mechanisms, a greater surface area or biodegradation. Baseline levels of competing natural organic matter surrogates (NOM) reduced overall adsorption efficacy but increasing concentrations of NOM did not impact metaldehyde removal efficacy in a significant way. Biological activated carbon was identified as the most suitable adsorbent of metaldehyde (94% removal) but sand with an acclimated biofilm was capable of acting as a bio-adsorbent of metaldehyde even under environmentally relevant concentrations (41% adsorption from 0.002.5 mg L−1). Moreover, we observed that thermal hydrolysis of metaldehyde occurred at 60 °C, suggesting that thermal regeneration of GAC for this pesticide was possible at relatively low temperatures. Biological adsorption and thermal hydrolysis approaches presented herein offered a way forward to increase efficiency and cost effectiveness of existing treatments for metaldehyde.